Pengenalan Ekonomi Berbasis Digital Yang Bermoral Pada Siswa TPQ Mesjid Nurul Ihsan Alai Timur Padang - Deni Amelia; Vivi Puspita Sari; Fitri Firdalius (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Technological progress is currently felt to be increasingly rapid, we can feel that progress in the field of technology is greatly influencing our daily lives. The digital economy is a form of technological development that is currently being enjoyed by various groups, including children, teenagers and adults. This digital economy is an economic activity carried out with the help of digital technology. One form of digital economic technology is the internet, Android-based cellphones/applications. Since Covid-19 happened, it has forced everyone to use gadgets to carry out all their activities, especially children from elementary school to university level, as well as TPQ children at the Nurul Ihsan Mosque when carrying out learning activities, they have to use gadgets to be able to carry out activities. from their respective homes with the aim of not gathering in one place (mosque). The use of digital economic technology is able to influence them, such as in the games and applications available. Basically, the use of this technology still has to be supervised by parents, but not all parents can monitor their children's use of this item so that even in our daily lives, the use of digital economic technology can influence the attitudes and ethics of children and teenagers.